Characterization of Residential Woodsmoke PM2.5 in the Adirondacks of New York - George Allen; Lisa Rector (Aerosol and Air Quality Research)
Abstract Although woodsmoke from residential wood heating can be the dominant source of winter PM2.5 in rural areas, routine monitoring is done primarily in urban or suburban areas. To obtain data on elevated woodsmoke concentrations from nearby sources, the PM2.5, black carbon at 880 and 370 nm, particle-bound polycyclic aromatic hydrocarbons (PAHs), and wind speed and direction were measured during winter at three residential locations in Saranac Lake, New York. A paired-site design enabled the identification of local sources relative to larger spatial scales. With the exception of occasional regional PM events, the hourly measurements of this pollutant between the paired sites exhibited poor correlations, suggesting that local woodsmoke was responsible for the observed increases in PM values. One location that was adjacent to a residence with a wood stove, which was 40 meters from the monitoring site, experienced repeated episodes of elevated PM2.5 concentrations, with a maximum 3-hour average of 150 µg m−3, a maximum 24-hour rolling average of 64 µg m−3, and a maximum midnight-to-midnight average of 46 µg m−3. Despite these PM events, the data indicated that this location was likely in compliance with the current U.S. EPA National Ambient Air Quality Standards (NAAQS) for PM2.5. The daily PM2.5 concentration peaked and troughed during the nighttime and the daytime, respectively, at all of the sites, which is consistent with local ground-level pollution sources, such as woodsmoke; this diel pattern was also confirmed by Aaethalometer Delta-C (DC) data, a woodsmoke PM indicator. The particle-bound PAH data was less specific than the DC data to the PM in the woodsmoke, partly because the instrument for the former also responds to traffic pollution. One site repeatedly displayed the influence of 2-cycle engine snowmobile exhaust during the early evening hours, with very high PAH concentrations but only modestly elevated DC concentrations. Subsequent tests showed that fresh 2-cycle small engine exhaust produces a somewhat weaker response than woodsmoke in the DC in terms of the concentration per unit of PM.